A company sells boxes of small blue pom-poms (b) for $42 and boxes of large orange pom-poms (p) for $52. They make batches of small blue pom-poms that fill 8 boxes and batches of large orange pom-poms that fill 4 boxes. The company only has 40 boxes. Which system of equations helps the company plan to make $350? b = 40 − p 8b + 4p = 40 b = 40 − p 42b + 52p = 350 8b = 40 − 4p 42b − 52p = 350 8b = 40 − 4p 42b + 52p = 350
So I got b= 42 p = 52 which I put in 8b + 4p = 40 42b + 52p = 350
Thats not one of the answers tho? Sorry ill space them out they look confusing
b = 40 − p 8b + 4p = 40 b = 40 − p 42b + 52p = 350 8b = 40 − 4p 42b − 52p = 350 8b = 40 − 4p 42b + 52p = 350
@Peaches15 I'm having trouble on the 2nd part do you know what it is?
Hurryyy I need to submit my exam >.<
yeesss. Math is my worst subject and my teacher is an retrice
Lol, I gotta take algebra 2 over the summer...
It might be D
Yeahh I'm trying to graduate this year so i'm trying to finish quick
@HydrogenCyanide I don't know dat sorry
It's good @Peaches15 thanks for helping tho, Like I said the nearest answer might be D
@HydrogenCyanide sorry im a little good in math
Okayy. Can you tell me how to solve itso I knoww
Sorry for wasting you're time @LexiLuvv2431, For that I give you a medal and a fan for cooperating with me.
Its okayy you didn't waste my time its okayy
It was right, thank youu
I do have an assignment I need help on, if you don't mind.
It has 3 parts, it has to do with parabolas
@AnimalLover8 @ali2x2 @bubbleslove1234 @dan815 @markaskingalexandria1 @Astrophysics @sweetburger @.Sam. @Owlcoffee help @LexiLuvv2431 plzzz
Pleasee I need this done quickkk
When you create the equation of a given graph, you take the roots and write it out as the factored form, the roots for the given parabola is \(x= -6 \) and \(x=6\) so writing it to the factorized form: \[(x +6)(x-6)+36=0\]
oh no, wait, it is just \[(x +6)(x-6)=0\]
So then whats the equation??
Do the distributive and you'll get it.
Oh gosh I suck at that >.< hold on
Okay i have no idea
\[(x +6)(x-6) \rightarrow x^2 -6x +6x-36\] Since it opens downwards it must meand that the "x^2" is negative: \[-(x^2-6x +6x-36)=0\] So, all you have to do is simplify that equation and youçll get the answer.